Decadal oscillation of autumn precipitation in Central Vietnam modulated by the East Pacific–North Pacific (EP–NP) teleconnection - R Li; S-Y Wang; R R Gillies; B M Buckley; L H Truong; C Cho (Environmental Research Letters, 2015)
Autumn precipitation over Central Vietnam is associated with an increase in the occurrence of tropical cyclones that lead to frequent flooding and pose a significant threat to lives and property. The present analyses reveal a pronounced decadal oscillation of autumn precipitation in Central Vietnam within the 8–11 year frequency band that is modulated by the East Pacific–North Pacific (EP–NP) teleconnection. The negative phase of the EP–NP pattern is associated with a positive sea surface temperature (SST) anomaly in the South China Sea (SCS) that induces low-level convergence, enhances convection, and increases precipitation over Central Vietnam and adjacent islands including Hainan (China) and the Philippines. This circulation feature around the SCS is embedded in a large-scale circulation associated with SST anomalies across the Pacific Ocean—i.e., cooling in the Eastern and Central tropical Pacific sandwiched by warming in the North and South Pacific as well as the Western Pacific Ocean. The positive phase of the EP–NP features opposite SST and circulation anomalies, with the result being reduced rainfall in Central Vietnam. This out-of-phase relationship and shared decadal spectral coherence between the EP–NP index and autumn precipitation in Central Vietnam might be useful for future climate predictions and flood management.